Another Side of Folk Tradition; Da’wah, Entertainment, and Magic in the Madurese Community - Acep Aripudin; Yaya Yaya (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2021)
The emergence and development of traditional arts is closely related to the process of spreading religion. Not always art in religious communities appears deductively as a development of the spirit of religious teachings. This is because, in fact, art in traditional societies is potentially produced and can become a medium as well as a tool in spreading religion and relationships as well as strengthening the character of the community. Cultural values in art are then unified and integrated into a local wisdom that complements each other, so that religious arts and culture are functionally inductively attached. This article aims to reveal how Islamic values as a religion are functionally related to the art traditions of the Madurese community. The position of art as something profane and entertaining then changed to follow the position of a sacred religion and had similar consequences. The form of the relation between art and Islam can be seen in song lyrics, the history of the emergence of art, moments of performing arts, art genres, the spread of religion and the legality of religious leaders. In the end, the traditional arts of the community were preserved as Islam was preserved, and even developed into a multi-force that has an impact on improving the community's economy. Keywords: Da'wah, Art, Entertainment, Ritual, Madura, and Local Wisdom Abstrak Muncul dan berkembangnya seni tradisional sangat berkaitan dengan proses penyebaran agama. Tidak selamanya seni pada masyarakat beragama muncul secara deduktif sebagai pengembangan dari spirit ajaran agama. Karena, dalam faktanya seni pada masyarakat tradisional secara potensial diproduksi dapat mejadi media sekaligus alat dalam menyebarkan agama dan dan huburan sekaligus yang memperkuat karakter masyarakat. Nilai-nilai budaya dalam seni kemudian menyatu dan terintegrasi menjadi suatu kearifan lokal yang saling mengisi, sehingga seni budaya beragama secara induktif melekat secara fungsional. Artikel ini, bertujuan mengungkap bagaimana nilai-nilai Islam sebagai agama berhubungan secara fungsional dengan tradisi seni masyarakat Madura. Posisi seni sebagai sesuatu hal yang profane dan menghibur kemudian berubah mengikuti posisi agama yang sacral dan memiliki konsekuensi serupa. Wujud relasi seni dan Islam nampak pada syair lagu, sejarah munculnya seni, momen-momen pentas seni, genre seni, penyebar agama dan legalitas dari pemuka agama. Seni tradisional masyarakat pada akhirnya terpelihara sebagaimana terpeliharanya Islam, bahkan berkembang menjadi kekuatan multi yang berdampak seperti pada peningkatan ekonimi masyarakat. Kata Kunci: Da’wah, Seni, Hiburan, Ritual, Madura, dan Kearifan Lokal